Evaluation of Toxoplasmosis in Female College Students - Wikandari, Ririh Jatmi; Afriansya, Roni; Kuncara, Rachmad Bayu; Afrianti, Dina; Setyowatiningsih, Lilik (Poltekkes Kemenkes Palu, 2024)
Female students are a group of women of childbearing age who can become pregnant and have risk factors for toxoplasmosis which can cause pregnancy disorders, birth defects, and death. Seroepidemiological studies of toxoplasmosis in women are essential to determine whether infection occurs in the early stages of fertilization or earlier. The research aimed to determine the incidence of toxoplasmosis in female college students. This research was carried out in June 2023 and has received ethical recommendations from KEPK Poltekkes Kemenkes Semarang. The type of research used was analytical descriptive. Sampling used purposive sampling. The inclusion criteria were 87 students who were willing to have their blood taken. Blood is taken using the venipuncture method, then the whole blood is separated from the plasma. Plasma samples were collected and analyzed for the presence of anti-Toxoplasma gondii using the ELISA method. Then the data was analyzed using SPSS software, univariate analysis to determine the frequency distribution and percentage of each variable. The results showed that 31 students were positive for IgG anti-Toxoplasma gondii. Of these, the majority aged 20 years (n = 20, 16.1%) were positive for anti-Toxoplasma gondii IgG. Toxoplasmosis infection of 9.2% occurred in female college students who owned cats, 3.4% occurred in female college students who consumed undercooked meat, and 29.8% of female college students who consumed raw vegetables. Female college students have risk factors for Toxoplasma gondii infection so it is important to carry out screening so that Toxoplasma gondii can be detected and treated immediately.